(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article analyzes media discourse in English and Uzbek from a communicative-pragmatic perspective. The work examines the communicative functions of modern media from a linguistic perspective, discourse strategies in a social and cultural context, speech acts, intensional meaning, presupposition, implicature, and the use of socio-pragmatic tools. The forms of implementation of pragmatic tasks such as conveying information, influencing, and forming beliefs in media texts are considered on a comparative basis in English and Uzbek samples.